ANALISIS EFISIENSI DAN STABILITAS KEUANGAN BANK SYARIAH DI INDONESIA - Aida, Aisatul; Antona, Khaerunnisa Filda; Anggraini, Meli Sapa; Yanka, Fira Dwi; Ati, A (Pusat Riset dan Publikasi, 2024)
This study aims to analyze the financial efficiency and stability of Sharia Banking in Indonesia. Dynamic economic development and regulatory challenges are still obstacles. Sharia Banking in Indonesia has experienced significant growth in recent decades due to increasing public awareness of sharia principles and government support for the sector. This study examines how Sharia Banking can achieve operational efficiency and optimal financial stability to survive in an increasingly competitive banking industry. This research uses a qualitative method with a literature research approach. Literature sources can be obtained from books, journals, magazines, research results (thesis and dissertation), and other relevant sources (internet, newspapers, etc.). The results of this study indicate that Sharia Banking in Indonesia tend to be more efficient and financially stable compared to conventional banks. High efficiency was achieved through optimal use of resources and adoption of technology. Good financial stability is reflected in healthy financial ratios and effective risk management. The results of this study can be a reference for developing strategies to improve the performance and competitiveness of Sharia Banking in the future.